Composition of the milk of yaks raised at different altitudes on the Qinghai–Tibetan Plateau. (August 2016) - Cui, G.X.; Yuan, F.; Degen, A.A.; Liu, S.M.; Zhou, J.W.; Shang, Z.H.; Ding, L.M.; Mi, J.D.; Wei, X.H.; Long, R.J.
Abstract: We examined the nutritional quality of milk from yaks raised at 3016, 3824 and 4750 m above sea level on the Qinghai–Tibetan plateau. The Trolox equivalent antioxidant capacity, vitamin A concentration, fat content, conjugated linoleic acid, γ-linolenic acid, total unsaturated fatty acids and Fe, Zn and Na concentrations of yak milk increased while vitamin C concentration, crude protein content and Cu and Mn concentrations decreased with increasing altitude. Also, the atherogenic index was lower at the middle and highest altitudes than at the lowest altitude. Thus, in general, there was an increase in nutritional quality in the milk with an increase in altitude. We concluded that the observed differences resulted from the combined effects of altitude, forage composition and forage availability. Crude protein in milk and forage both decreased while fat in milk and neutral detergent fibre in forage both increased with increasing altitude.